Sustained Reduction in Urgent Care Antibiotic Prescribing During the Coronavirus Disease 2019 Pandemic: An Academic Medical Center's Experience. (22nd January 2022) - Ha, David; Ong'uti, Sharon; Chang, Amy; Mui, Emily; Nelligan, Ian; Betts, Brooke; Lentz, Christopher; Alegria, William; Fox, Emily; Meng, Lina; Stenehjem, Edward; Hersh, Adam L; et al.
Abstract: We compared antibiotic prescribing before and during the coronavirus disease 2019 (COVID-19) pandemic at 2 academic urgent care clinics and found a sustained decrease in prescribing driven by respiratory encounters and despite transitioning to telemedicine. Antibiotics were rarely prescribed during encounters for COVID-19 or COVID-19 symptoms. COVID-19 revealed opportunities for outpatient stewardship programs.